Incident of Intradialytic Hypertension and Quality of Life in Hemodialysis Patient - Sutra Dewi; Hidayati Hidayati; Mulyastuti Mulyastuti; Disa Hijratul Muharramah (Indonesian Journal of Global Health Research, 2024)
Intradialytic hypertension is an often overlooked complication during hemodialysis, yet it possesses the potential to increase morbidity and mortality among CKD patients undergoing routine hemodialysis, indirectly impacting their quality of life. This study aims to analyze the occurrence of intradialytic hypertension and its impact on the quality of life of hemodialysis patients. Employing a Case-Control design, the research subjects consisted of patients with intradialytic hypertension as the case group and those without intradialytic hypertension as the control group. The study population comprised CKD patients undergoing hemodialysis at DR M. Djamil Padang Hospital. The sampling technique employed was convenience sampling, with a total sample size of 44 individuals, evenly divided into two groups of 22 patients each (hypertension and non-hypertension). Data analysis included both univariate and bivariate analyses. The questionnaire utilized was KDQOL-SF version 1.3. Bivariate analysis results indicated a difference in the quality of life of hemodialysis patients between those with and without intradialytic hypertension (IHD). Activation of educational initiatives and the utilization of educational media, such as audio-video materials and leaflets provided by various Healthcare Professionals (HCPs), are recommended to enhance the quality of life of hemodialysis patients.